A novel direction control method for walking support with an omnidirectional walker. (13th April 2015) - Jiang, Yinlai; Wang, Shuoyu; Ishida, Kenji; Ando, Takeshi; Fujie, Masakatsu G.
Safe and convenient walking support machines are strongly desired for the people suffering from walking disabilities. We have developed an omnidirectional walker (ODW) for walking support. In walking support, it is necessary to control the ODW following the user's directional intention. In this paper, a novel interface is proposed to recognise the user's directional intention according to the forearm pressures. The forearm pressures exerted to the ODW by the user with wrists and elbows are measured by four force sensors embedded in the ODW's armrest. The relationship between the forearm pressure and the directional intention was extracted as fuzzy rules and an algorithm was proposed for directional intention identification based on distance-type fuzzy reasoning method. We conducted a path tracking experiment with the proposed method. The results show that the algorithm is applicable to control the ODW in walking support.